Enzymatic constituents in crossbred buck semen - KALE, M M; TOMER, O S (The Indian Journal of Animal Sciences, 2013)
A study was conducted an 10 crossbred buck’s (Alpine x Beetal (7), Saanen x Beetal (1) semen for 5 enzymatic constituents (HYL, GOT, GPT, AKP, ACP) during 3 seasons. Season significantly (P<0.05) affected HYL, GOT, GPT and AKP activity. Bucks differed in their GPT, ACP and AKP constituents and the season x buck interaction influenced all the 5 enzymatic constituents of buck semen. Association of enzyme activity and aero somal damage was noticed. The overall mean enzyme activity in the extracellular fluid was hyaluronidase (0.71 +-0.05 umole/ml), GOT(1.40 Â± 0.42 mole/ml), GPT (1.63 Â± 0.11 mmole/ml), ACP (25.12 Â± 1.80 mmole/ml) and AKP (53.70 Â±3.34 mmole/ml).